Guardians’ Attitudes towards Online Class in Ditel Rupakot Majhuwagadhi Municipality - Rai, Shyam Kumar (DMC Journal, 2022)
Lockdown (COVID-19) brought changes in the mode of teaching and learning process. It transformed traditional classes to digital classes. Digital classes are new to the students, guardians and teachers in our society. It might have positive and negative impacts. To find the attitude of guardians towards online classes is the main concern of this study. Its findings assist to the educational planners, teachers and guardians for better improvement of digital classes. The target population for this study were selected from the guardians of Diktel Rupakot Majhuwagadhi Municipality. Stratified and random sampling procedures were applied for the study. Close ended questions were structured and administered to the respondents. The hypothesis of this study was expected to be positive but the result is negative. Almost 80% guardians showed their attitude unsatisfactorily. To make effective and productive digital classes, proper management is highly demanded from local to national government. Lack of trained teachers, insufficient digital devices and its services to the guardians, lack of digital knowledge about handling it are the major obstacles to conduct digital classes.